A multi pathway coupled domino strategy: I2/TBHP-promoted synthesis of imidazopyridines and thiazoles via sp3, sp2 and sp C–H functionalization. Issue 10 (17th February 2022) - Wang, Yishou; Li, Shichen; Wang, Xinfeng; Yao, Yiming; Feng, Lei; Ma, Chen
Abstract : One-pot, multi-pathway, and atom economic synthesis of imidazoles and thiazoles has been achieved. In the catalytic system, I2 /TBHP as an initiator and oxidant is used to realize sp 3, sp 2 and sp C–H functionalization. Abstract : I2 /TBHP-promoted, one-pot, multi pathway synthesis of imidazopyridines and thiazoles has been achieved through readily available ethylarenes, ethylenearenes and ethynearenes. I2 /TBHP as an initiator and oxidant is used to realize the C–H functionalization of this domino reaction. Simple and available starting materials, wide range of functional group tolerance, high potential for drug activity of the products and application in production are the advantageous features of this method.